Exponential Mesh Approximations for a 3D Exterior Problem in Magnetic Induction (Journal of Computational Mathematics, 2005)
A numerical method combining the approaches of C.I. Goldstein and L.-A. Ying is used for the simulation in three-dimensional magnetostatics related to an exterior problem in magnetic induction. Recently introduced, this method is based on the use of a graded mesh obtained by gluing homothetic layers in the exterior domain and has been performed in the case of edge element discretizations. In this work, the theoretical and practical aspects of the method are inspected in the case of face element and volume element discretizations, for computing a magnetic induction. Error estimates, implementations, and numerical results are provided.